Mucoadhesive-floating zinc-pectinate–sterculia gum interpenetrating polymer network beads encapsulating ziprasidone HCl. (20th October 2015) - Bera, Hriday; Boddupalli, Shashank; Nayak, Amit Kumar
Highlights: Zn-pectinate–SG IPN beads containing ziprasidone HCl were developed. The beads were prepared by ionotropic gelation and covalent crosslinking method. A 3 2 full factorial design was adopted to optimize the beads. The responses of the optimized beads were in accordance with the predicted values. The IPN beads showed excellent gastroretention and sustained drug release profile. Abstract: A novel dual crosslinked low-methoxyl (LM) pectinate–sterculia gum (SG) interpenetrating polymer network (IPN) beads was developed for intragastric ziprasidone delivery. The IPN beads were accomplished by simultaneous ionotropic gelation with zinc acetate and covalent crosslinking with glutaraldehyde. The effects of pectin and SG contents on drug entrapment efficiency (DEE, %), and cumulative drug release after 8 h ( Q 8, %) were studied to optimize the IPN beads using a 3 2 factorial design. The optimized beads encapsulating ziprasidone HCl (F-O) displayed DEE of 87.98 ± 1.15% and Q8 of 58.81 ± 1.50% with excellent buoyancy (floating lag time <2 min, % buoyancy at 8 h >63%) and good mucoadhesivity with the goat gastric mucosa. In most cases, the drug release behaviour obeyed Higuchi kinetics with anomalous transport mechanism. The Zn–pectinate–SG IPN beads were also characterized by SEM, FTIR, DSC and P-XRD analyses.